Level of Self-Care and Patient Care Against COVID-19 Among Emergency Medical Services Personnel; a Cross-sectional Study - Sirvan Abbasi Ghocham; Sina Valiee; Naser Kamyari; Salam Vatandost (Archives of Academic Emergency Medicine, 2023)
Introduction: Provision of pre-hospital care by emergency medical services (EMS) requires paying attention to self-care and patient care against possible infections. The present study was conducted with the aim of determining the level of self-care and patient care against COVID-19.